1987
DOI: 10.1002/ajim.4700110309
|View full text |Cite
|
Sign up to set email alerts
|

Death certificate‐based occupational mortality surveillance in the united states

Abstract: Surveillance of cause-specific mortality patterns by occupation and industry through the use of death certificate records is a simple and relatively inexpensive approach to the generation of leads as to potential occupational disease problems. Researchers from the National Institute for Occupational Safety and Health (NIOSH) have been working with the National Center for Health Statistics, other federal agencies, and state health departments on a number of programs to foster the development of standardized, ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 27 publications
(9 reference statements)
0
22
0
2
Order By: Relevance
“…In addition to its well-established design for studying proportionate deaths from cancer, other strengths of this investigation included its (1) lack of financial sponsorship by major MMA manufacturers, many of whom supported earlier no-excess cancer cohort studies; (2) exact confirmation of death for all study decedents using both professional association and NDI registries; (3) use of four-digit, not three-digit, ICD-9 CPT codes with the highest confirmation (>80%), detection (>80%), and nosological (≥97%) match rates for determination of cancer as underlying causes of death based on histopathological diagnoses; and (5) control-to-case ratio of 4:1 using socioeconomically matched general surgeons as controls in similar occupations without MMA exposures and with assumed similar lifestyle cancer risks from alcohol use, diet, and smoking [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its well-established design for studying proportionate deaths from cancer, other strengths of this investigation included its (1) lack of financial sponsorship by major MMA manufacturers, many of whom supported earlier no-excess cancer cohort studies; (2) exact confirmation of death for all study decedents using both professional association and NDI registries; (3) use of four-digit, not three-digit, ICD-9 CPT codes with the highest confirmation (>80%), detection (>80%), and nosological (≥97%) match rates for determination of cancer as underlying causes of death based on histopathological diagnoses; and (5) control-to-case ratio of 4:1 using socioeconomically matched general surgeons as controls in similar occupations without MMA exposures and with assumed similar lifestyle cancer risks from alcohol use, diet, and smoking [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Dubrow, Sestito, Lalich, Burnett, and Salg (1987) indicated that the use of DCs is a cost-effective and simple approach to the preliminary investigation of occupational disease surveillance. Burnett and Dosemeci (1994) pointed out that the strengths of DCs stem from their wide spread use, while the limitations include lack of accuracy and incomplete data.…”
Section: Background and Significancementioning
confidence: 99%
“…4 The pioneering efforts of Dr. Samuel Milham in his studies of occupational mortality in Washington State5 6 established the feasibility and utility of this approach on a state-specific basis.…”
Section: Occupational Mortality Surveillancementioning
confidence: 99%